ELDER MISTREATMENT AND SOCIAL NETWORK COMPOSITION. (11th November 2018) - Lees, K; McGuire, J; Griffith, J; Molnar, B
Abstract: The importance of social support for health is well documented in the literature. Recent evidence suggests that older adults are able to maintain dynamic social networks and that dense social networks are protective against mistreatment. However, there is a lack of research on consequences of elder mistreatment on social network composition. This study utilizes data from Waves 1 and 2 of the National, Social Life, Health, and Aging Project to model associations between elder mistreatment and net change in network size and network density, and to assess associations between perpetrator network position and victim depressive symptom scores at Wave 2. The results of these studies show statistically significant associations between mistreatment and network member gain, and that having a perpetrator within the close social network is positively associated with victim depressive symptoms scores. These results and implications for intervention and policy efforts will be discussed.